The diagnostic value of ADC histogram and direct ADC measurements for coexisting isocitrate dehydrogenase mutation and O6-methylguanine-DNA methyltransferase promoter methylation in glioma - Xie, Zhiyan; Li, Jixian; Zhang, Yue; Zhou, Ruizhi; Zhang, Hua; Duan, Chongfeng; Liu, Song; Niu, Lei; Zhao, Jiping; Liu, Yingchao; Song, Shuangshuang; Liu, Xuejun (Frontiers in Neuroscience, 2023)
Objectives: To noninvasively predict the coexistence of isocitrate dehydrogenase (IDH) mutation and O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation in adult-type diffuse gliomas using apparent diffusion coefficient (ADC) histogram and direct ADC measurements and compare the diagnostic performances of the two methods. Materials and Methods: A total of 118 patients with adult-type diffuse glioma who underwent preoperative brain magnetic resonance imaging (MRI) and diffusion weighted imaging (DWI) were included in this retrospective study. The patient group included 40 patients with coexisting IDH mutation and MGMT promoter methylation (IDHmut/MGMTmet) and 78 patients with other molecular status, including 32 patients with IDH wildtype and MGMT promoter methylation (IDHwt/MGMTmet), one patient with IDH mutation and unmethylated MGMT promoter (IDHmut/MGMTunmet) and 45 patients with IDH wildtype and unmethylated MGMT promoter (IDHwt/MGMTunmet). ADC histogram parameters of gliomas were extracted by delineating the region of interest (ROI) in solid components of tumors. The minimum and mean ADC of direct ADC measurements were calculated by placing three rounded or elliptic ROIs in solid components of gliomas. Receiver operating characteristic (ROC) curve analysis and the area under the curve (AUC) were used to evaluate the diagnostic performances of the two methods. Results: The 10th percentile, median, mean, root mean squared, 90th percentile, skewness, kurtosis and minimum of ADC histogram analysis and minimum and mean ADC of direct measurements were significantly different between IDHmut/MGMTmet and the other glioma group (P<0.001 to P=0.003). In terms of single factors, 10th percentile of ADC histogram analysis had the best diagnostic efficiency (AUC=0.860), followed by mean ADC obtained by direct measurements (AUC=0.844). The logistic regression model combining ADC histogram parameters and direct measurements had the best diagnostic efficiency (AUC=0.938), followed by the logistic regression model combining the ADC histogram parameters with statistically significant difference (AUC=0.916) and the logistic regression model combining minimum and mean ADC (AUC=0.851). Conclusions: Both ADC histogram analysis and direct measurements have potential value in predicting the coexistence of IDHmut and MGMTmet in adult-type diffuse glioma. The diagnostic performance of ADC histogram analysis was better than that of direct ADC measurements. The combination of the two methods showed the best diagnostic performance.